Perancangan Sistem Enkripsi dan Dekripsi File Dokumen Berbasis Web Pada Google Drive Menggunakan Algoritma Advanced Encryption Standard (AES) - Kosat, Ignasius; Anastasia, Jessica; Sifa, Mayela K.; Sallu, Falentina; Bona, Maria O. (Blantika: Multidisciplinary Journal, 2025)
Data security is a very important aspect, especially when using storage services such as Google Drive. Although Google Drive is equipped with an encryption system, users still need additional protection to ensure the security of their files. This study aims to design and develop a web-based system that can encrypt and decrypt documents using the AES (Advanced Encryption Standard) algorithm. Files supported by this system include text files (.txt), Word documents (.docx), PowerPoint (.pptx), and Excel (.xlsx). The developed system provides an intuitive interface, including an auto-upload feature that allows users to directly upload encrypted files to Google Drive by simply clicking the button provided. This integration aims to improve the user experience in securing data, as well as prevent potential unauthorized access from other parties who may have access to file links on Google Drive without user permission. This system works by encrypting files before they are uploaded to Google Drive and decrypting files after they are downloaded, so that only users who have access can open the files. The system creation process is carried out through several stages, starting from needs analysis, interface design, integration with Google Drive, to testing. The test results show that the system functions well and is able to maintain the security of user files. This system can be an additional solution to protect files stored on Google Drive.